1982
DOI: 10.1111/j.1365-3180.1982.tb00145.x
|View full text |Cite
|
Sign up to set email alerts
|

A study on seed population dynamics of three weedy species of Eupatorium

Abstract: Summary The data on seed population dynamics of three weedy species of Eupatorium, viz. E. adenophwrum Spreng., E. riparium Regel and E. odoratum L. have been presented and discussed in the paper. The seed production and seed populations in soil seed bank were estimated, and the fate of buried seeds in soil was followed over a 2‐year period. All the three species of Eupatorium produced a large number of seeds. The seed production of E. riparium per unit area was higher than that of the other two species becaus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
1

Year Published

1987
1987
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 15 publications
1
10
0
1
Order By: Relevance
“…The different responses of black nightshade (seedling emergence and survival) to soil mois-Volume 37, Issue 3 (May ), 1989 ture at cotton emergence make it difficult to accurately predict the competitive outcome of cotton and black nightshade, and the amount of control that is needed to protect cotton from this weed. This difficulty is not unique to the findings of this study, since others have reported that the competitive success of a crop or weed can be modified by environmental conditions, some of which are associated with management (1,20,26,35,46).…”
Section: Cottonmentioning
confidence: 82%
“…The different responses of black nightshade (seedling emergence and survival) to soil mois-Volume 37, Issue 3 (May ), 1989 ture at cotton emergence make it difficult to accurately predict the competitive outcome of cotton and black nightshade, and the amount of control that is needed to protect cotton from this weed. This difficulty is not unique to the findings of this study, since others have reported that the competitive success of a crop or weed can be modified by environmental conditions, some of which are associated with management (1,20,26,35,46).…”
Section: Cottonmentioning
confidence: 82%
“…Native to Mexico, this apomictic (Bala & Gupta, ; Hao et al, ), triploid Asteraceae (Baker, ; Bala & Gupta, ) grows gregariously as a subshrub in moist tropical and subtropical mountainous regions across the globe (Stone, Smith, & Tunison, ; Wan et al, ; Wang & Wang, ; Yu et al, ). It adversely affects native biodiversity (Ding, Xu, & Liu, ), livestock (Parsons & Cuthbertson, ; Tian, Feng, & Liu, ) and agricultural productivity (Parsons & Cuthbertson, ; Yadav & Tripathi, ) of the infested regions. It was initially introduced as an ornamental plant in the 19th and 20th centuries in several countries such as Australia (Auld, ), India (Bhatt, Singh, Singh, Tripathi, & Kohli, ), South Africa (Kluge, ), and the USA (Fuller, ) where it had naturalized and had further spread rapidly to neighbouring regions.…”
Section: Methodsmentioning
confidence: 99%
“…The initial step of our analysis was to build a robust database of occurrence data for A. adenophora covering the native Mexican range and four seriously invaded areas across the globe: USA, Asia (India and China), Canary Islands and Australia (Auld, ; Osorio, Scholz, & Torre, ; Parsons & Cuthbertson, ; Wang & Wang, ; Yadav & Tripathi, ). We extracted data from two global occurrence databases, namely GBIF (Global Biodiversity Information Facility, https://www.gbif.org/) and REMIB (Red Mundial De Información Sobre Biodiversidad, http://www.conabio.gob.mx/remib/cgibin/clave_remib.cgi?lengua=EN).…”
Section: Methodsmentioning
confidence: 99%
“…Ces résultats sont similaires à ceux de Kushwaha et al (1981), Yadav & Tripathi (1982) qui considèrent la régression de Chromolaena odorata comme le résultat d'une compétition inter et intraspécifiques. Toutefois, Slaats et al (1996), Holm et al (1977) et Audru et al (1988) ont montré que la durée de la jachère est pertinente.…”
Section: Discussionunclassified